Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep24069
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analyses of seven anurans reveal functions and adaptations of amphibian skin

Abstract: Animal skin, which is the tissue that directly contacts the external surroundings, has evolved diverse functions to adapt to various environments. Amphibians represent the transitional taxon from aquatic to terrestrial life. Exploring the molecular basis of their skin function and adaptation is important to understand the survival and evolutionary mechanisms of vertebrates. However, comprehensive studies on the molecular mechanisms of skin functions in amphibians are scarce. In this study, we sequenced the ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 55 publications
7
43
0
Order By: Relevance
“…According to the results of GO terms, basic biological and metabolic processes were largely enriched. Similar findings have been reported in frogs (Zhang et al, 2009;Huang et al, 2016). Additionally, amphibian skin has evolved complex structures and functions that allow amphibians to live in both water and land (Chuong et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…According to the results of GO terms, basic biological and metabolic processes were largely enriched. Similar findings have been reported in frogs (Zhang et al, 2009;Huang et al, 2016). Additionally, amphibian skin has evolved complex structures and functions that allow amphibians to live in both water and land (Chuong et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that amphibian skin secretions have anti-inflammatory, antibacterial, and antioxidant functions, and promote wound healing (Konig et al, 2015;Xu and Lai, 2015). Until now, the studies on the transcriptome (Huang et al, 2016), antioxidant peptidomes (Yang et al, 2009) and secretomes (Thompson et al, 2007) and proteomes (Wu et al, 2011) of frog skin have made great progress. In this study, we generated proteomics data of the newt skin using two-dimensional electrophoresis and MALDI-TOF/MS, and compared the protein kinds and expression values in the newt and giant salamander skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these factors combined with the absence of genomic information for L. boringii would have caused the failure of functional annotation of a part of the identified unigenes. However, considering that previous studies successfully annotated approximately 25,000 genes in other non-model amphibian species, such as Odorrana margaretae , Megophrys sangzhiensis and Rhacophorus omeimontis [34, 37], our gene annotation results (more than 29,000 unigenes annotated) from L. boringii ’s transcriptome can be considered as high quality.…”
Section: Resultsmentioning
confidence: 97%
“…The "general function" category (3,166; 24.37%) represented the largest group, 454 followed by "defense mechanisms" (1,421; 10.94%). Our results showed that genes related to defense 455 functions may be relatively abundant in the transcriptome of O. cruralis, particularly compared to the 456 seven anurans studied by Huang et al (2016) and also to A. mexicanum (Wu et al 2013 Although large genome size renders complete genome sequencing practically unfeasible in many 515 species, such as most amphibians, transcriptome sequencing represents a cost-effective alternative to 516 obtain a large amount of genome-wide data. This can allow advances in the study of ecological and 517 evolutionary processes beyond the limits imposed by the use of small panels of markers.…”
mentioning
confidence: 99%